2023
DOI: 10.1021/acs.jpclett.3c00966
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Carrier Dynamics of Evaporated Bismuth-Based Chalcogenide Thin Films Probed with Time-Resolved Microwave Conductivity

Abstract: Chalcogenide-based semiconductors are emerging as a set of highly promising candidates for optoelectronic devices, owing to their low toxicity, costeffectiveness, exceptional stability, and tunable optoelectronic properties. Nonetheless, the limited understanding of charge recombination mechanisms and trap states of these materials is impeding their further development. To fill this gap, we conducted a comprehensive study of bismuth-based chalcogenide thin films and systematically investigated the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, Yang and coauthors reported that the optoelectronic properties are highly dependent on the composition of ternary chalcogenides prepared via precursor route. We have to note that Bi 2 S 3 thin films exhibited relatively high charge carrier mobility and extremely long carrier lifetime . However, Bi 2 S 3 -based solar cells, or more broadly photodiodes, have barely been reported.…”
mentioning
confidence: 94%
“…Furthermore, Yang and coauthors reported that the optoelectronic properties are highly dependent on the composition of ternary chalcogenides prepared via precursor route. We have to note that Bi 2 S 3 thin films exhibited relatively high charge carrier mobility and extremely long carrier lifetime . However, Bi 2 S 3 -based solar cells, or more broadly photodiodes, have barely been reported.…”
mentioning
confidence: 94%